Role of N6-Methyladenosine (m6A) Methylation Regulators in Hepatocellular Carcinoma - Qu, Nanfang; Bo, Xiaotong; Li, Bin; Ma, Lei; Wang, Feng; Zheng, Qinghua; Xiao, Xuhua; Huang, Fengmei; Shi, Yuanyuan; Zhang, Xuemei (Frontiers in Oncology, 2021)
Liver cancer is the fifth most common malignant tumor in terms of incidence and the third leading cause of cancer-related mortality globally. Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer. Although great progress has been made in surgical techniques, hepatic artery chemoembolization, molecular targeting and immunotherapy, the prognosis of liver cancer patients remains very poor. N6-methyladenosine (m6A) is the most abundant internal RNA modification in eukaryotic cells and regulates various stages of the RNA life cycle. Many studies have reported that the abnormal expression of m6A-related regulators in HCC represent diagnostic and prognostic markers and potential therapeutic targets. In this review, firstly, we introduce the latest research on m6A-related regulators in detail. Next, we summarize the mechanism of each regulator in the pathogenesis and progression of HCC. Finally, we summarize the potential diagnostic, prognostic and therapeutic value of the regulators currently reported in HCC.